On Lacunarity in Translation of Culture Specific Concepts - Lyubymova, Svitlana; Tomasevich, Nadezhda; Mardarenko, Olena (Transletters. International Journal of Translation and Interpreting, 2018)
A socio-cultural stereotype is a specific culture concept, distributed by a language community in form of implications completely or partially unintelligible for representatives of other cultures. This specific fragment of a national “world picture”, called lacuna, presents much difficulty in translation. Lacunarity of a sociocultural stereotype in interlingual translation is determined by lexical, cultural, historical, and social factors. Decomposition of a stereotype pragmatic information into components enables to emphasize relevant for a particular context feature, which is possible to render by means of translation language. Reproducing noticeable implications is of special importance for reproduction of a pragmatic meaning of sociocultural stereotypes.